THE EFFECTIVENESS OF RASPBERRY PI- BASED ELECTRIC PRACTICAL LEARNING IN ENHANCING INTEREST TOWARDS PHYSICS AMONG PRE-UNIVERSITY STUDENTS - Abdullah, Aslindawati; Abdullah, Nurul Syafiqah Yap; Yaacob, Mohd Ikhwan Hadi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates the effectiveness of a Raspberry Pi-Based Electric Practical Learning, supported by the use of Rasphy Comic as a practical manual in improving Pre-University students’ interest in Physics laboratory learning. The quasi-experimental research involved 134 students and applied pre-test and post-test measures to assess the impact of the intervention. Wilcoxon Signed-Ranks Test revealed that the median score for students’ interest in Physics laboratory learning after the implementation of Raspberry Pi (Med = 83) was significantly higher than the median score before the intervention (Med = 59), with Z = -9.763, p = .000. Based on the significance level set at α = 0.05, the data analysis indicates a statistically significant difference in students’ levels of interest in Physics laboratory learning before and after the Raspberry Pi-Based Electric Practical Learning intervention. These findings suggest that the application of Raspberry Pi had a positive impact on enhancing students’ interest in learning Physics laboratory activities.